(untitled) (LACCEI, 2024)
The present research work is developed with the purpose to determine the influence that the time study has on the improvement of labor productivity in the picking process in a logistic operator, using a quantitative research. Likewise, a convenience sampling was developed, having a total population of 96,822 items collected in a supermarket in Lima-Perú, there was a sample of 13,049 items during the period of July and September 2021. Finally, after the implementation, the labor productivity during the picking process reach the expected daily ratio of 50 items/HH, allowing the company to reduce the overtime generated by pickings not carried out, likewise, the economic analysis gives us a NPV of S/ 12,030.75, an IRR of 85.57% and a Benefit-cost of 1.20, allowing the viability of the project.